EFEKTIFITAS METODE EKSPERIMEN BERBASIS MEDIA PRESENTASI DALAM MENINGKATAN CAPAIAN BELAJAR SISWA - Frindi L Morontong; Patricia M. Silangen; Alfrie M. Rampengan (Charm Sains: Jurnal Pendidikan Fisika, 2022)
Education is the key to all quality progress and development, because with education humans can realize all their potential both as individuals and as citizens of society. This study aims to describe the application of an experimental method based on presentation media at Efata Bambung Christian Middle School. This study uses a class action research method, the subject of the research is class VIII students, totaling 38 students. This research was carried out in two cycles and each cycle had two meetings. This research was carried out in April of the 2019/2020 school year according to the time of physics subjects at school. Through the results of this study, using an experimental method based on presentation media can increase student involvement in learning and be able to increase student learning outcomes. The more stable students' understanding of the material presented by the teacher so that it can improve classical learning completeness from cycle I to 50% and cycle II to 100%. In the second cycle, classical student learning completeness has been achieved. The research can be concluded that the experimental method based on presentation media has a positive impact in improving student learning outcomes which is marked by an increase in student learning mastery in each cycle.